From Mummers to Madness A Social History of Popular Music in England, c.1770s to c.1970s - Taylor, David (University of Huddersfield Press, 2021)
From Mummers to Madness surveys the evolution of popular music in England from the mid-Georgian to mid-Elizabethan years. It considers the major socio-economic and technological developments that impacted profoundly on the production and consumption of music, and seeks to explain how popular music both shaped and responded to these changes.